2013
DOI: 10.1002/cncr.28141
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival advantage with partial nephrectomy: A bias of observational data?

Abstract: the Urologic Diseases in America ProjectBACKGROUND: Partial nephrectomy (PN) and radical nephrectomy (RN) are standard treatments for a small renal mass. Retrospective studies suggest an overall survival (OS) advantage, however a randomized phase 3 trial suggests otherwise. The effects of both surgical modalities on OS were evaluated compared with controls. METHODS: A matched cohort study was performed using the Surveillance, Epidemiology, and End Results (SEER)-Medicare dataset. Individuals treated with PN or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 36 publications
7
43
0
1
Order By: Relevance
“…This is in line with previously published population-based analyses and it has been partially explained by the preservation of renal function with partial nephrectomy [5,[24][25][26]. However, this apparent superiority of partial nephrectomy has been challenged by the possibility of observational selection bias in these retrospective studies [27]; given the fact that patients referred for partial nephrectomy are more likely to be of earlier Tumor Node Metastasis (TNM) stage and/or more geographically favorable location compared to those referred for total nephrectomy and also given the fact that patients referred to ablative treatment are usually medically inoperable because of co-morbidities. Thus, plenty of confounding factors may hinder definite conclusions based solely on retrospective studies.…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with previously published population-based analyses and it has been partially explained by the preservation of renal function with partial nephrectomy [5,[24][25][26]. However, this apparent superiority of partial nephrectomy has been challenged by the possibility of observational selection bias in these retrospective studies [27]; given the fact that patients referred for partial nephrectomy are more likely to be of earlier Tumor Node Metastasis (TNM) stage and/or more geographically favorable location compared to those referred for total nephrectomy and also given the fact that patients referred to ablative treatment are usually medically inoperable because of co-morbidities. Thus, plenty of confounding factors may hinder definite conclusions based solely on retrospective studies.…”
Section: Discussionsupporting
confidence: 88%
“…Showing identical survival rates, PN showed a better renal function preservation in their collective [11] . These survival rates are confirmed by recent studies on this topic [12][13][14] . Concerning renal function, other studies confirm that PN is associated with a better preservation of renal function [7,[13][14][15][16][17][18] .…”
supporting
confidence: 77%
“…This indicates that the patients included in these nonrandomized studies were different from the start, meaning that those selected for PN were 'better' patients who obviously had less cardiovascular disease and therefore had better cardiovascular outcomes. Another study confirmed that both PN and RN impact on cardiovascular disease [7], whilst another meta-analysis showed no difference for cardiovascular outcomes [8]. Obviously patients with preoperative CKD will benefit from nephron-sparing surgery [9], as well as those who have concomitant conditions, e.g.…”
mentioning
confidence: 56%